Museums as cultures of copies the crafting of artefacts and authenticity - Brenna, Brita; Christensen, Hans Dam 1965- ,editor; Hamran, Olav (Routledge research in museum studies, 2019)
Few institutions are warier of copies than museums. Few fields of knowledge are more prone to denounce copies as fake than the heritage field. Few discourses are as concerned with authenticity, aura, originals and provenance as those concerning exhibiting and collecting. So why is it that these are institutions, fields and discourses where copies proliferate and copying techniques have thrived for hundreds of years? Museums as Cultures of Copies aims to make the copying practices of museums visible and to discuss, from a range of interrelated perspectives, precisely what function copies fulfil in the heritage field and in museums today.